Measurement model of e-SQ dimensions and users' satisfaction in Malaysia IHL - Al-Nuaimi, I.T.I. (Institute of Electrical and Electronics Engineers Inc., 2016)
Quality of e-service is one of the critical factors that decide the success or failure of organizations. It may increase competitive advantages as well as enhance the relationships with the customers. Achieving high e-service quality and user satisfaction are challenging since they depend fundamentally on user perception and expectation which can be tricky at times. To date, there is no agreement as to what service quality is, and how it should be measured, whether it is a function of statistical measures of quality including physical defects or managerial judgment, or it is a function of customer perception about the services. This paper deep-dived the quality of e-services offered by five Malaysian Institutes of High Learning (IHL) including two private and three public universities. A quantitative approach was utilized to collect the data and AMOS 21 was used to analyze the data and develop the measurement model. The paper aims to find the relationship between e-service quality dimensions and the user satisfaction by using Conformity Factor Analysis (CFA) test with 320 students in the target universities. The research results indicated that the measurement model has acceptable values and ready to conduct the Structural Equation Model (SEM) for the relationship between e-SQ dimensions and user satisfaction. Achieving high user satisfaction can enhance the competitive advantage of the universities in their respective target markets. Â© 2016 IEEE.